A Quadrilateral Shaped Fractal Slot Planar Antenna for Ultra-Wide Band Applications. Issue 3 (3rd July 2022) - Kumar, Ranjeet; Sinha, Rashmi; Choubey, Arvind; Mahto, Santosh Kumar
ABSTRACT: This paper presents a low-profile quadrilateral-shaped fractal slot planar antenna using a novel fractal geometry where circular, triangular and regular hexagonal motifs are iterated to form antenna elements. It consists of a partial ground plane and a triangular fractal-shaped patch fed by a microstrip line having an I-shape rectangular slot to increase the bandwidth. A compact 32 × 22 mm 2 fractal antenna proposed here is investigated to evaluate its performance in ultra-wideband (UWB) applications. The bandwidth of 15.5 GHz ranging from 3.57 GHz to 19.07 GHz with voltage standing wave ratio (VSWR) less than 2 in the entire operating band is achieved. Simulated values of realisable gain (6.8 dBi), impedance bandwidth (15.5 GHz), radiation efficiency (90%), radiation patterns and group delay evaluation indicate that the discussed antenna is favourable for UWB applications such as world interoperability microwave access, wireless local area network, 5 G, X-band, C-band, S-band and Ku-band. The proposed antenna is fabricated, and measured results are compared with simulated results as well as with those reported in the literature.